The Role of Stakeholders in Empowering Farmer Groups in Dempo Tengah District, Pagar Alam City, South Sumatra Province (Case Study in Gapoktan Beguyur) (International Journal of Scientific Research and Management (IJSRM), 2025)
Empowerment is an effort to provide power (empowerment) or strengthening to the community. This study aims to analyse the role of stakeholders in empowering coffee farmer groups in Dempo Tengah District, Pagar Alam City, South Sumatra. The main focus of the research is to identify how the government, private sector, and the farmer groups themselves contribute to enhancing the technical and marketing capacities of coffee farmers. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and documentation. Informants consist of key stakeholders, namely representatives from t h e government, private sector (NGOs and coffee business actors), and members of the Gapoktan Beguyur farmer group. Data were analysed using MAXQDA software to identify themes and patterns of actor involvement. The results show that the government plays a dominant role as a facilitator, regulator, and dynamizer through the provision of technical training, production facilities, and access to financing. The private sector serves as a strategic partner in downstream processing, branding enhancement, and market access through packaging design training, digital marketing, and product promotion. Meanwhile, the farmer groups play a crucial role in internal consolidation, joint production management, and strengthening social capital to support the sustainability of empowerment programmes. Collaboration among stakeholders has proven to enhance farmers’ abilities to manage their farming businesses independently and expand market networks.